What story should a history of popular music tell? - Moore, Allan (Popular Music History, 2004)
Histories of ‘popular music’ abound: stories of agents whose medium of public expression is music (i.e. accounts of the dealings and output of singers, writers, producers, label executives etc.). Because these stories take as their subjects the succession of individuals who produce work, rather than the work successive individuals produce, there is little challenge to the practice of hyping every change as ‘new’, since both audiences and, frequently, practitioners, have a vested interest in being unaware of historical precedents. However, these are not histories of ‘popular music’: stories of the behaviour of sounds which constitute aesthetic objects are vital to provide context for the work of analysts. What might such a history look like? It might be a history of the issues to which musical decisions give rise (genre formation; the decision-making relationship between ‘writer’ and ‘performer’ etc.). It might be a history of recurring patterns of aesthetic intentions (successive turns to sophistication and simplicity in the realms of lyrics, technology, harmonic language etc.). It might be a history of styles (of the ways musical materials are moulded) and of the conditions for their apparent demise. Such histories can be conceived: one such is demonstrated.